2010
DOI: 10.1002/ijc.25612
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput live‐cell imaging reveals differential inhibition of tumor cell proliferation by human fibroblasts

Abstract: Increasing evidence indicates that cancer development requires changes both in the precancerous cells and in their microenvironment. To study one aspect of the microenvironmental control, we departed from Michael Stoker's observation (Stroker et al, J Cell Sci 1966;1:297-310) that normal fibroblasts can inhibit the growth of admixed cancer cells (neighbour suppression). We have developed a high-throughput microscopy and image analysis system permitting the examination of live mixed cell cultures growing on 384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 36 publications
5
74
0
Order By: Relevance
“…There is increasing evidence that cancer-associated fibroblasts (CAFs) are "educated" by cancer and converted to a phenotype that promotes cancer growth (15)(16)(17)(18)(19)(20)(21). However, CAFs are heterogeneous (17,22), and several reports have shown that fibroblasts inhibit cancer cell proliferation through generation of soluble factors or direct cellular contact (23)(24)(25). We were curious whether fibroblasts in cancer are capable of producing cytoguardins.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that cancer-associated fibroblasts (CAFs) are "educated" by cancer and converted to a phenotype that promotes cancer growth (15)(16)(17)(18)(19)(20)(21). However, CAFs are heterogeneous (17,22), and several reports have shown that fibroblasts inhibit cancer cell proliferation through generation of soluble factors or direct cellular contact (23)(24)(25). We were curious whether fibroblasts in cancer are capable of producing cytoguardins.…”
Section: Resultsmentioning
confidence: 99%
“…39 Recent studies have also demonstrated that normal human fibroblasts can inhibit the proliferation of tumor cells. 40,41 We hypothesize that these 'protective' fibroblasts could also preserve the AR dependence of PCa cells after ADT. Moreover, Banerjee et al demonstrated that epigenetic changes in prostatic fibroblasts could cause DNA damage, mediating prostate tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that stromal ablation of the tumour suppressor Pten during mammary carcinogenesis results in accelerated tumourigenesis, via Ets2 inactivation, suggesting multiple pathways by which fibroblasts can inhibit neoplastic growth [30,31]. In vitro co-culture studies using primary normal fibroblasts isolated from various human tissues, when cultured with human prostate, lung, and lymphoblastoid tumour cell lines, support a role for fibroblasts in restricting the proliferative potential of tumour cells in a contact-dependent manner [32]. Some of the growth-inhibiting activity provided by fibroblasts may be directly associated with their role as sentinel cells, capable of 'sensing' tissue damage, associated with aberrant epithelial proliferation: Experimental analysis using a mouse model of intestinal inflammation revealed that colonic fibroblasts express NLRP6 (NOD-like receptor family pyrin domain containing 6), a stress-associated molecular pattern recognition receptor.…”
Section: From Tumour Suppressors To Tumour Promotersmentioning
confidence: 93%